Absolution : a Southern Reach novel - VanderMeer, Jeff (VanderMeer, Jeff. Southern Reach trilogy., 2024)
"A continued exploration of the mysterious Area X by the scientists and voyagers that VanderMeer introduced ten years ago in the original volumes"--